STRENGTH ANALYSIS OF SHEARER DRUM CUTTING GANGUE COAL ROCK BASED ON LS-DYNA - LIU XuNan; ZHAO LiJuan; ZHOU WenChao; LIU HongMei (Jixie qiangdu)
To obtain the stress information of the spiral drum of the thin coal seam shearer under the complicated condition,and then guide the design of its parameters or the matching of kinematic parameters. The models of drum and coal rock were established by PRO/E,and imported to ANSYS through a dedicated interface. According to the actual situation,the operation of adding elements,material,meshing grid,restriction and contact were done. Finally,the coupling model of the spiral drum cutting gangue coal rock was established in LS-DYNA. Set the hauling speed was 4 m/min,the drum speed was 80 r/min,and the dynamic simulation was carried out. The contact force information and the stress contours of the corresponding parts were obtained. The results show that: the maximum stress of cutting alloy heads,picks,holders and blades are 1209. 26 MPa,812. 5 MPa,371. 79 MPa and 103. 56 MPa,respectively,which are less than the allowable stress of each material,and can work reliably. This method can find the weak link of the drum,and can provide important theoretical reference for the design of the spiral drum and the matching of its kinematic parameters.